Body mass index and wealth index: positively correlated indicators of health and wealth inequalities in Nairobi slums. (4th June 2018) - Haregu, T. N.; Mohamed, S. F.; Muthuri, S.; Khayeka-Wandabwa, C.; Kyobutungi, C.
Abstract : Introduction: Wealth index is a known predictor of body mass index (BMI). Many studies have reported a positive association between BMI and socioeconomic status (SES). However, an in-depth investigation of the relationship between BMI and wealth index is lacking for urban slum settings. Objective: To examine the association between BMI and wealth index in an urban slum setting in Nairobi, Kenya. Methods: A total of 2003 adults between 40 and 60 years of age were included. BMI was derived from direct weight and height measurements. Wealth Index was computed using the standard principal component analysis of household amenities ownership. The relationship between BMI and wealth index was assessed using both linear and logistic regression models. Results: We found that BMI linearly increased across the five quintiles of wealth index in both men and women, after adjusting for potential confounding factors. The prevalence of obesity increased from 10% in the first wealth quintile to 26.2% in the fifth wealth quintile. The average BMI for women entered the overweight category at the second quintile wealth status, or the third quintile for the total population. Conclusion: There exists a strong positive relationship between BMI and wealth index in slum settings. Health promotion interventions aimed at reducing obesity may consider using wealth index in priority setting.